Is the use of Cannabis associated with periodontitis? A systematic review and meta‐analysis. (24th January 2019) - Chisini, Luiz A.; Cademartori, Mariana G.; Francia, Alejandro; Mederos, Matias; Grazioli, Guillermo; Conde, Marcus C. M.; Correa, Marcos B.
Abstract : Recent studies have shown that there is also biological plausibility for a possible relationship between periodontal disease and Cannabis use, thus the aim of this study was to investigate whether the use of Cannabis is associated with periodontitis. Electronic searches were performed in PubMed, Scopus, ISI‐Web of Science, BVS‐Virtual health library and Scielo without restrictions. Search strategy was performed using relevant keywords considering the structure of each database. Longitudinal and cross‐sectional studies that investigated the association between the use of Cannabis and periodontal disease were included. Meta‐analyses and sensitivity analysis were conducted. A total of 143 records were found in the initial searches and five articles were included in the systematic review, being four studies included in the meta‐analysis. Overall, 13 491 individuals were included, of which 49.5% were males. Three of included studies investigated the relationship between cannabis and periodontal disease in adults and the other two studies were performed in adolescents. A positive association was observed between the use of cannabis and periodontitis (PR 1.12 CI 95% [1.06‐1.19]) with 19.0% of heterogeneity. The analysis of sensibility showed that none study influenced the results enough to change the pooled estimate. Regarding to the quality assessment, all studies presented high quality. The results of systematic review and meta‐analyses demonstrate that the use of Cannabis is associated with a higher prevalence of periodontitis.